Pengaruh Debt To Equity Ratio, Price To Earning Ratio, dan Dividend Payout Ratio terhadap Price Book Value Perusahaan Subsektor Hotel, Restoran, dan Pariwisata yang Terdaftar di Bursa Efek Indonesia Pada Periode 2016-2020 - Kumba Digdowiseiso; Falya Azkia Putri (Syntax Corporation, 2022)
The study aims to determine and analyze the effect of the Debt to Equity Ratio, Price to Earning Ratio, and Dividend Payout Ratio on the Price Book Value of Hotels, Restaurants, and Tourism Subsector Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The data source of this research is secondary data in the form of financial reports obtained from the IDX and from the company's website. The research sample was 20 companies with the method used was purposive sampling method. The research data analysis technique used panel data regression analysis using the STATA 16 program. The results showed that partially there was a significant positive effect between Debt to Equity Ratio and t Price Book Value, partially there was an insignificant positive effect between Price to Earning Ratio and Price Book Value, partially there is an significant negative effect between Dividend Payout Ratio and Price Book Value. Debt to Equity Ratio, Price to Earning Ratio, and Dividend Payout Ratio simultaneously have no significant effect on Price Book Value.